Efecto del calcio y azufre en el sistema de maíz-frijol en ladera ante un nivel de nitrógeno y fósforo en El Salvador 1989 - Sosa M., José Heriberto (2016)
Two field experiments were established in 1988 at Opico Quezaltepeque, El Salvador, on volcanic-ash derived soils to evaluate maize and bean grain yield response to applied sulfur, calcium and potasium. Also under evaluation was the effect of burning crop residues (common practice in this area) compared to zero tillage. The common system employed in this region is a maize-bean relay whereby the maize is planted in May and the beans in August. Four cycles of data were obtained at both locations (2 Maize, 2 beans). The treatments consisted of various combinations of ammonium sulfate and urea with and without sulfur, calcium and potasium. Grain yields were higher when ammonium sulfate (100 kg N/ha) was joint band applied with formula (16-20-0, 30 kg P2O5 ha) under zero tillage. When this same treatment was evaluated when residues were burned, grain yields were significantly lower. When comparing ammonium sulfate snd urea jointly applied with phosphorus a possible response to sulfur was noted on these soils. Aplications of potasium did not increase grain yields of either maize or beans. When dolomitic limestone was applied at arate of 3 tons/ha, no significant differences were found in maize grain yields, however, a significant bean yield increase was found the second year compared with the no lime treatment.